A smart model for web attendance: contactless technology / Haslinda Noradzan, Siti Nurbaya Ismail and Mahfudzah Othman - Noradzan, Haslinda; Ismail, Siti Nurbaya; Othman, Mahfudzah (Research Management Institute (RMI), 2013)
Students' attendance records are important documents for academic institutions that reflect the students' performances and the credibility of the institutions. This research discusses the feasibility study that has been done in UiTM Pahang to identify the problems of recording and reporting students' attendances using manual attendance system. In this study, 550 respondents ranging from the lecturers, students and the management of UiTM Pahang have taken part in the fact-finding process through distributions of questionnaires. From the findings, a well-managed system is indeed needed to be reinforced in order to make the process of recording and reporting the attendances more efficient. This research discusses the development of the proposed Smart Model Attendance Register System (SMART) by adapting the System Development Life Cycle (SDLC) methodology. The new system is being developed involving the integration of various open source web-based technologies such as MySQL, PHP and Apache Web Server and accordingly making the system more efficient and cost effective. The new system consists of automated processes such as ability to generate online attendance reports, warning letters and graph charts thus making the processes of recording and reporting the students' attendances more efficient and well-organized.